2018
DOI: 10.1002/ejic.201800504
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structures, and Catalytic Activity of Homo‐ and Heteroleptic Ketoiminate Zinc Complexes in Lactide Polymerization

Abstract: The heteroleptic complex LZnEt [(1); L = MeNacac = MeNC(Me)CHC(Me)O] containing the sterically less demanding N,O-chelating ketoiminate (MeNacac) ligand was synthesized by reaction of ZnEt 2 with an equimolar amount of MeNacacH, whereas the reaction with two equivalents MeNacacH gave the homoleptic complex L 2 Zn 5. 1 reacts with ArOH (Ar = 2,6-Me 2 -Ph) with ethane elimination and formation of LZnOAr (2). Addition of the Lewis base dmap (dmap = 4-dimethylamino pyridine) to 1 and 2 yielded the corresponding Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Our group is committed to seeking such a multifunctional catalyst. Metal zinc represents one of the most attractive candidates due to its inexpensive, nontoxic, and biocompatible advantages. Most of the reported zinc catalysts in ROP require the participation of delicate and complicated supporting ligands, such as β-diiminate Zn complex synthesized by Coates, to improve the reactivity and controllability, by changing the steric resistance and electrical properties of the central metal. The synthesis of ligands increases the cost of catalysts and therefore reduces their practice industry application value. Herein, we report a catalyst based on a simple, supporting ligand-free zinc bis­[bis­(trimethylsilyl)­amide].…”
Section: Introductionmentioning
confidence: 99%
“…Our group is committed to seeking such a multifunctional catalyst. Metal zinc represents one of the most attractive candidates due to its inexpensive, nontoxic, and biocompatible advantages. Most of the reported zinc catalysts in ROP require the participation of delicate and complicated supporting ligands, such as β-diiminate Zn complex synthesized by Coates, to improve the reactivity and controllability, by changing the steric resistance and electrical properties of the central metal. The synthesis of ligands increases the cost of catalysts and therefore reduces their practice industry application value. Herein, we report a catalyst based on a simple, supporting ligand-free zinc bis­[bis­(trimethylsilyl)­amide].…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the metal substituents as well as the electron‐donating substituents of the pyrrolidine‐ β ‐ketoiminate ligands play an important role in the activity and stereoselectivity of the polymerization process. Recently, we reported the ROP of LA by using homoleptic (L 2 Zn) and heteroleptic (LZnOAr) β ‐ketoiminate zinc complexes and demonstrated that the heteroleptic complexes LZnOAr containing a supplementary phenoxide or Lewis base coordinated to the Zn atom are highly active catalysts . In addition, a large number of β ‐ketoiminate metal complexes were reported, which showed excellent reactivity to the ROP of cyclic esters under milder reaction condition in a controlled mechanism…”
Section: Introductionmentioning
confidence: 99%
“…These findings demonstrate that the reaction rates of the alcoholysis reaction of 1 and 2 with BnOH are comparable. Comparing the catalytic activity of fluorinated β ‐ketoiminate zinc complex 2 in the ROP of lactide with that of non‐fluorinated β ‐ketoiminate zinc analogues [5a] clearly shows, that the introduction of electron‐withdrawing CF 3 and C 6 F 5 groups to the β ‐ketoiminate ligand backbone reduces the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%